2021
DOI: 10.7759/cureus.18290
|View full text |Cite
|
Sign up to set email alerts
|

Doppler-Assessed Ureteric Jet Frequency: A Valuable Predictor of Ureteric Obstruction

Abstract: Objectives: To compare ureterovesical jet frequency in non-obstructed versus obstructed ureter secondary to ureteric stone using ultrasonography in patients presenting with ureteral stones.Study design: Cross-sectional prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…The absence or decreased frequency of ureteral jets may indicate urinary obstruction. The severity of ureteric obstruction can be determined by evaluating all jet dynamics, including velocity, duration, and frequency[ 64 ]. However, computed tomography is still the most diagnostic tool of Po-AKI due to benign and malignant causes[ 5 ].…”
Section: Diagnosismentioning
confidence: 99%
“…The absence or decreased frequency of ureteral jets may indicate urinary obstruction. The severity of ureteric obstruction can be determined by evaluating all jet dynamics, including velocity, duration, and frequency[ 64 ]. However, computed tomography is still the most diagnostic tool of Po-AKI due to benign and malignant causes[ 5 ].…”
Section: Diagnosismentioning
confidence: 99%
“…18,19 Further studies have shown that the urinary jet flow velocity in the obstructive ureter is significantly lower than that in the non-obstructive side. [20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler examinations were first performed in patients with hydronephrosis with a urinary jet examination 18,19 . Further studies have shown that the urinary jet flow velocity in the obstructive ureter is significantly lower than that in the non‐obstructive side 20–22 …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, considering reno ureteral stones as the most prominent case of obstructive uropathy, initial ultrasonography has been proven to have a similar efficacy to initial abdominopelvic CT with less associated radiation in high-risk diagnosis[ 35 ]. Additionally, with the use of Doppler Ultrasound, it is possible to evaluate the presence of ureteral jets in the bladder; the absence or decreased frequency of these suggests the presence of urinary obstruction[ 36 ].…”
Section: Etiology and Diagnostic Challengesmentioning
confidence: 99%